PENGARUH CITRA TOKO TERHADAP KEPUASAN PELANGGAN DAN LOYALITAS PELANGGAN (Studi Pada Ritel Toko Avia Malang) - Oktavianto, Reynaldi (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2017)
Retail store is a solution for the problems faced by people dealing with their personal needs. It offers speed and accuracy in fulfilling consumer’s needs. It also beneficial for the consumers in terms of the time they have to spend for shopping for daily needs. The objectives of this study are 1) to assess the influence of store image on customer satisfaction; 2) to assess the influence of store image on customer loyalty; 3) to assess the influence of satisfaction on loyalty; 4) to assess the influence of store image on customer loyalty through customer satisfaction. This survey research is carried out on customer of Toko Avia in Malang. The respondents of this study are 130 customers who have stopped in Toko Avia. The instrument of analysis used in this study is Partial Least Square (PLS). The results of the analysis show that the variable of store image has a significant relation with the customer satisfaction. Customer satisfaction has a significant relation with customer loyalty. Merchandise is one of the indicators that play an important role in shaping the perception of customer on store image. Services relevant to the expectation of customer is one of the indicators that play an important role in shaping the perception of customer on loyalty. This show that, in building customer loyalty, store image needs to be improved because the image will affect satisfaction, and satisfaction will improve customer loyalty.Keywords: Store Image, satisfaction, loyalty, retail store, PLS, merchandise, services